Agricultural Export and Macroeconomic Factors in Nigeria: The Bound Test Approach - Oyetade, Oluwatoyese Oluwapemi; Asaleye, Abiola; Popoola, Olabisi; Lawal, Adedoyin (International Journal of Energy Economics and Policy, 2020)
There has been many significant research efforts that have been devoted to understand the effects of macroeconomic factors on the agriculture in Nigeria. Thus, macroeconomic factors such as exchange rate and crude oil price over the period 1981 to 2016 examined the effects on agricultural export in Nigeria. This paper employed the ARDL bound test analysis since all the macroeconomic series used in the study are of mixed integrated order of stationarity. A Granger causality was also carried out in order to examine whether there is any predictive power of crude oil price for agricultural export. The findings showed that there exists a significant relationship between the agricultural export which is the dependent variable and the exchange rate but not in the case of the crude oil price. It also revealed that the variables do cause each other in some directions. In conclusion, there is long run relationship between exchange rates and agricultural export in Nigeria. Keywords: Agriculture export, Macroeconomics factors, Crude oil price, Exchange rate JEL Classifications: B22, B27, B41 DOI: https://doi.org/10.32479/ijeep.7148